Development and validation of UV spectrophotometric method for orbifloxacin assay and dissolution studies - Cazedey, Edith Cristina Laignier [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Univ Sao Paulo, Conjunto Quimicas, 2014)
New, simple and cost effective UV-spectrophotometric method was developed for the estimation of orbifloxacin in pharmaceutical formulation. Orbifloxacin was estimated at 290 nm in 0.5 M hydrochloric acid. Linearity range was found to be 1.0-6.0 mu g mL(-1). The method was tested and validated for various parameters according to main guidelines. The proposed method was successfully applied for the determination of orbifloxacin in tablets. The results demonstrated that the procedure is accurate, precise and reproducible, while being simple, economical and less time consuming. It can be suitably applied for the estimation of orbifloxacin in routine quality control and dissolution studies.

Um método espectrofotométrico novo, simples e de baixo custo foi desenvolvido para a determinação de orbifloxacino em formulação farmacêutica. O orbifloxacino foi determinado em 290 nm utilizando ácido clorídrico 0,5 M como solvente. O intervalo de linearidade usado foi de 1,0 a 6,0 μg mL–1. O método foi testado e validado em vários parâmetros de acordo com os principais guias. O método proposto foi aplicado com sucesso para a determinação de orbifloxacino em comprimidos. Os resultados demonstraram que este procedimento é exato, preciso e reprodutível, ao mesmo tempo em que é simples, barato e de mais rápida execução e pode ser adequadamente aplicado para a determinação de orbifloxacino na rotina do controle de qualidade e em estudos de dissolução de comprimidos contendo este fármaco.
Keywords: Medicines/quality control; Medicines/dissolution; Orbifloxacin/determination; UV spectrophotometry/quantitative analysis/validation; Medicamentos/controle de qualidade; Medicamentos/dissolução; Método analítico; Orbifloxacino/determinação; Espectrofotometria na região do UV/controle de qualidade/validação